REWARD AND PUNISHMENT IN ENGLISH FOREIGN LANGUAGE CLASSROOM - Wan Muthia Lubis; Irma Dewi Isda; Chairuddin Chairuddin; Evi Zulida; Rahmiati Rahmiati; Surya Asra (Journal of Education, Linguistics, Literature and Language Teaching, 2019)
This research aimed to find out of reward and punishment used by teacher in English Foreign Language classroom and to find out reward and punishment implementation by teacher in English Foreign Language classroom. The method used in this research is descriptive qualitative research. This research was analyzed kinds of reward and punishment in efl classroom and the implementation of reward and punishment. The sample of this research is one of the English Teacher at SMPN 2 Kejuruan Muda and focus on eight grades (VIII-1) Classroom. And the final result of this research is kinds of reward that used by teacher in English Foreign Language classroom is verbal reward, non verbal reward, reward with come close to students, reward with touch, gifth, and reward with fun activities. Punishment that used by teacher in English Foreign Language classroom is preventive punishment and repressive punishment. Implementation of reward and punishment in English Foreign Language classroom that used by teacher is: First, teacher prepared the lesson material to gives for students. Second, teacher gives an explanation of the lesson material to students. Third, in the middle of the explanation of the material the teacher giving the practice questions in accordance with the subject matter given. Fourth, for students who are active in class, and answer correctly get certain reward according to those given by the teacher. The teacher only gives four ways in implementing reward and punishment in efl classroom, but the teacher does not implement the method five and six. Keyword: reward, punishment, implementation, English foreign language classroom.